AN INVESTIGATION ON THE VIRTUAL PROTOTYPING VALIDITY – SIMULATION OF GARMENT DRAPE - Lapkovska, Eva; Dabolina, Inga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Achievement of desired garment form is essential in the development of clothing design, which depends on properties of its raw material - mainly fabric. Virtual prototyping can serve as a tool for assessing the form and fit of garments before real production and deciding whether to make changes in ease values, pattern cut or fabric parameters. The aim of the study is investigation of reliability of virtual prototyping results using Modaris 3D (Lectra) due to influences of changeable fabric parameters on garment drape effects, as well as verifiability with three-dimensional (3D) scanning (Vitus Smart XXL®) of real products. For the research half-circle cut skirt designed in appropriate size for standard figure dummy. Skirt virtually simulated on mannequin which previously scanned and imported into the system. Properties of three different types of fabrics examined in a material testing laboratory according to requirements of relevant standards. Skirt virtually tried-on defining fabric properties by gained testing results and afterwards made from real fabrics, put on the dummy and scanned. Drape effects of the various virtual prototypes and real product scans compared, both in the CAD system and the scanning system (Anthroscan) using cross-sections and their measurements (depths and diameters of folds, circumferences). Fabric parameters has an influence on the reliability of virtual prototyping results in terms of accuracy of parameters determined and put into the system. Cross-sections with measurements reveal differences between virtually sewn and real skirt drape configurations.